Real-World Three-Year Clinical Outcomes of Biolimus-Eluting Stents versus Other Contemporary Drug-Eluting Stents in Patients with Acute Myocardial Infarction Patients: Data from the Korea Acute Myocardial Infarction Registry (KAMIR) - Ji Young Park; Seung-Woon Rha; Yung-Kyun Noh; Byoung Geol Choi; Ji Yeon Hong; Jae-Woong Choi; Sung Kee Ryu; Sung-Hun Park; Yong Hoon Kim; Myung Ho Jeong (Journal of Interventional Cardiology)
Introduction. Biolimus-eluting stents (BES) are known to be superior to bare-metal stents. This study aims to evaluate the safety and efficacy of BES compared to other drug-eluting stents (DES) based on big data from the Korea Acute Myocardial Infarction Registry (KAMIR). Methods. The study analyzed a total of 9,759 acute myocardial infarction (AMI) patients who underwent percutaneous coronary intervention (PCI) with DES. Total death, cardiac death, recurrent MI, revascularization, stent thrombosis, target lesion failure (TLF, composite of cardiac death, recurrent myocardial infarction (MI), and target lesion revascularization), and major adverse cardiac events (MACE, composite of total death, recurrent MI, and revascularization) were analyzed in patients with AMI up to three years. Study populations were divided into BES (n = 2,020), everolimus-eluting stents (EES, n = 5,293), and zotarolimus-eluting stents (ZES, n = 2,446) groups. Results. To adjust baseline potential confounders, an inverse probability weighting (IPTW) analysis was performed. After IPTW, at three years, total death (7.2%, 8.6%, and 9.5%, P<0.001), cardiac death (4.1%, 5.3%, and 6.6%, P<0.001), recurrent MI (1.6%, 2.6%, and 3.2%, P<0.001), TLF (6.5%, 8.1%, and 9.1%, P<0.001), and MACE (15.8%, 17.5%, and 18.2%, P<0.001) were lowest in the BES group compared with the other DES groups in AMI patients. During the 3-year clinical follow-up, the BES group showed better outcomes of MACE (hazard ratio (HR), 0.773; 95% confidence interval (CI), 0.676–0.884; P<0.001), TLF (HR, 0.659; 95% CI, 0.538–0.808; P<0.001), total death (HR, 0.687; 95% CI, 0.566–0.835; P<0.001), and cardiac death (HR,0.593; 95% CI, 0.462–0.541; P<0.001) than the EES groups. Conclusions. In this study, BES was superior to EES or ZES in reducing total death, cardiac death, TLF, and MACE in AMI patients.